National book of Belarus in the context of globai book culture: the conception of the book museum in Minsk - Sapiega, Tatjana (Knygotyra, 2003)
Belarus has its deep and rich traditions in the field of the book-printing craft. The humane role of the book was perfectly well understood by the medieval book lovers: Eufrasinja Polatskaja, Kiryta Turauski, Kliment Smatjatych and Auramij Smalcnski. The work of Belarusian and East Slavic printer Francis Skaryna facilitated the democratization of the book, its aesthetic beauty, intelligibility and availability. The Belarusian founder of printing and his followers: S. Budny, V. Tsiapinsky, P. Mscistavicc, V. Hataburda, Mamonich brothers, the printers of the Jesuit’s printing houses rose and confirmed the significance of the book craft of Belarus in the whole European Renaissance. Belarusian book museums are to show all the book heritage of Belarusian people as a unique event of Slavic and European culture, a monument of the past ages, a manifestation of the spiritual creative work of the people and an invaluable treasure, of which the descendants can be proud. In Polotsk, one of the eldest cities of the East Slavs and the native town of E. Polatskaja, F. Skaryna enlighteners and the book printer Symeon Polatsky, a Belarusian printing museum was established. It is situated in the restored building of the former Jesuit’s school, which is an architectural monument of the end of the 18th century. This museum was opened in 1990. Its exposition occupies 14 halls and tells the visitors about the history of the book in social, technical and artistic aspects from the ancient times till today. The beginning of the museum exposition presents the monuments of a non-book written language, Belarusian manuscripts, its repertory, and style of the artistic makeup. The main part of the exposition shows the life and activity of the Belarusian founder of printing F. Skaryna and his fellows. Separate rooms of the museum are dedicated to the history of the development of written language, paper, cover, book illustration, artistic makeup of a book etc. There are book and non-book exhibits such as: household articles, instruments of the work bound up with book making, photos, works of painting and graphics, copyist work shop of the 16th–18th c., scientifically reconstructed, printing house of the same centuries, modern studio of a book artist etc. The museum of Belarusian Printing in Polotsk is the only book museum in Belarus. The National Library of Belarus (NLB) is preparing to open a Book Museum, which will be based on the stocks of the Department of Manuscripts, Rare and Old Printed Books of NLB in Minsk. That’s why the foundation of the museums in the greatest libraries is natural, because they have the rich book collections and many other exhibits. So the libraries think about the utilization of its resources. The museum attached to the library gives a possibility to join the book monument’s preservation and the maximum opening of the stock. The Book museum exposition is planned to be founded with the goal to show the book in its variety as a complex occurrence that is a product both of spiritual and material spheres of the human activity. The museum exposition will be grounded on the chronological and thematic principles. A visitor will have a possibility to see a historical development of the book art from the beginning of the written language to the modern information carriers. The museum exposition will be based on the original editions and manuscripts. The Department of Manuscripts, Rare and Old Printed Books numbers near 65 units of storage. The Book museum in Minsk will differ from that one in Polotsk because the Belarusian book in it will be represented in European context. One will see both a unique character of Belarusian culture and its unity with European traditions. To achieve this aim the national exhibits will find their places with the books from different countries of Europe. In order that the Belarusian book will not be lost in the chronological section it is necessary to distinguish it by any artistic way. Only the Museum can help to show the universality and national peculiarity of the book and make it available to the general public.